Understanding and Measuring Symptom Burden in Heart Failure: A Concept Analysis. (October 2019) - Stockdill, Macy L.; Patrician, Patricia A.; Bakitas, Marie
Heart failure is a common, complex, and costly condition accompanied by a high degree of symptom burden. The concept of heart failure symptom burden has been used and measured inconsistently in research. To develop effective symptom management and palliation strategies, a clear conceptual understanding is needed. Rodgers' evolutionary method of concept analysis was used to identify articles in CINAHL, Embase, Scopus, and PubMed focused on chronic heart failure. Analysis of 20 articles revealed key attributes (subjectivity, negative impact on daily life and/or overall functioning, synergistic symptom associations, and symptom exacerbation), related terms (symptom distress and symptom experience), a surrogate term (heart failure burden), antecedents (heart failure classification or stage), and consequences (increased morbidity/mortality, decreased functioning, increased symptom prevalence/severity, decreased quality of life, and recurrent hospital admissions). No gold standard for measurement was identified. Research is needed to validate heart failure symptom burden measurement strategies across populations.